2019
DOI: 10.1186/s12873-019-0236-3
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits in older patients: a population-based survey

Abstract: Background Given the higher incidence of emergency conditions in older inhabitants, the global increase in aged population will pose a challenge for emergency services. In this study we examined the burden caused to emergency health care by the aged population. Methods Consecutive patients aged 80 years or over visiting a high-volume, collaborative emergency department (ED) between 2015 and 2016 were included. The key factors under analysis were the incidence of emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 9 publications
4
84
0
Order By: Relevance
“…However, other studies conducted in western countries showed that females were more likely to visit emergency departments compared with male, and agree with our findings that older patients were likely to visit emergency departments [9][10][11][12][13] . The explanation for variations in predominance of males in our study compared with other studies may due to the nature of structure of our community in which males are more engaged in public activities and employment, particularly in military services.…”
Section: Discussionsupporting
confidence: 93%
“…However, other studies conducted in western countries showed that females were more likely to visit emergency departments compared with male, and agree with our findings that older patients were likely to visit emergency departments [9][10][11][12][13] . The explanation for variations in predominance of males in our study compared with other studies may due to the nature of structure of our community in which males are more engaged in public activities and employment, particularly in military services.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with findings by Ukkonen et al . (2019) [ 41 ]. Further findings by this present study, which show that 48.3% (n=143) and 36.1% (n=107) of the patients were admitted for further management and discharged from the ED, respectively suggests that the levels of medical conditions of the majority of elderly patients who visited the BDH ED were mild to moderate.…”
Section: Discussionmentioning
confidence: 99%
“…The care of older patients in the emergency department (ED) is often complex due to comorbidity, polypharmacy [1], cognitive and functional decline. In addition, older patients are frequent visitors who often present atypical symptoms, require more extensive diagnostic workup, stay longer in the ED, and are more often admitted to inpatient care [2][3][4][5]. Research on innovative care models for older ED patients is therefore a high priority [6].…”
Section: Introductionmentioning
confidence: 99%